A binary mixture of a biosurfactant and an ionic liquid surfactant as a green dispersant for oil spill remediation - Shah, M.U.H. (2019)
Formulations based on conventional surfactants and organic solvents have been used as potential dispersants for oil-spill remediation. However, their toxicity restricts their usage in marine environments. As a low-toxicity alternative, in this article we report an oil dispersant based on a binary mixture of an ionic liquid surfactant, choline laurate (ChoLau), and a biosurfactant, lactonic sophorolipid. We investigated the micellar properties, including the critical micelle concentration, micellar interaction parameter (Î²), and activity coefficients (f 1 and f 2 ) for the mixed surfactant system. A non-ideal and synergistic interaction between ChoLau and lactonic sophorolipid was observed. A stable oil-in-water emulsion formed at an optimal ratio of 40:60 (w/w) of ChoLau and lactonic sophorolipid. At this ratio, a dispersion effectiveness of 83% was achieved with a dispersant-to-oil ratio of 1:25 (v/v). We observed the dispersed oil droplets with an optical microscope and evaluated their size using dynamic light scattering. The droplet size decreased with increasing dispersant-to-oil ratio. We also assessed the toxicity of the binary surfactant mixture in zebra fish (Danio rerio). Based on this assessment, the mixture can be classified as non-toxic. Therefore, the mixture of ChoLau and lactonic sophorolipid is a potential alternative to conventional toxic oil-spill dispersants. Â© 2019 Elsevier B.V.